Hypothetical learning trajectory trigonometry based on problem-based learning with Jambi Malay ethnomathematics nuances - Hamdani, Vikri; Armiati, Armiati; Arnawa, I Made; Jamaan, Elita Zusti (Universitas Islam Raden Intan Lampung, INDONESIA, 2023)
Background: Trigonometry is a challenging subject for many high school students. Incorporating cultural relevance, such as Jambi Malay ethnomathematics, into teaching can be a way to facilitate understanding. This study focuses on developing a hypothetical learning trajectory (HLT) tailored to Class X high school students on the topic of trigonometry.Aim: The primary goal of this research is to create a valid, practical, and effective HLT for trigonometry based on problem-based learning, integrating the nuances of Jambi Malay culture.Method: This study employed a combination of two design research models: the Plomp model and the Gravemeijer and Cobb model. The research was conducted in three stages: 1) initial investigation, 2) product development, and 3) assessment. Expert validation and practical testing were carried out to assess the quality of the HLT.Result: Validation by experts indicated that the developed HLT achieved a score of 3.69, falling into the